Always look on the bright side of life: Individual differences in visual attentional breadth for understanding temperament and emotion regulation in adolescents - Van Beveren, Marie-Lotte; Braet, Jolien; De Raedt, Rudi; Grol, Maud; Wante, Laura; Braet, Caroline (Frontiers in Psychology, 2023)
Introduction Cognitive-affective models of depression show that negative and positive emotionality differentially confer risk for depression through maladaptive and adaptive emotion regulation (ER) strategies respectively. Yet, no research has examined the mechanisms through which these temperament traits shape individual differences in ER. The current study explored the mediating role of attentional breadth for emotional information in the distinct pathways from temperament to ER strategies in adolescents. Methods The hypotheses were tested in a selected sample of 71 adolescents (M = 14.15, SD = 1.90; 62% girls) using a previously validated measure of visuospatial attentional breadth. Results First, positive emotionality was positively associated with attentional breadth for positive stimuli and temperamental vulnerable adolescents showed deficits in the processing of positive stimuli when presented far from the center of the visual field. Second, attentional breadth towards neutral stimuli was positively related to adaptive ER strategies. Third, no evidence was found for the proposed mediation models. However, post-hoc analyses provided preliminary evidence for a reversed mediation model in which adaptive ER strategies mediate the relationship between temperament and attentional breadth towards neutral stimuli. Discussion The results underscore the apparent complexity of the relations between temperament, attentional breadth, and ER and point out the need for further research in order to inform early intervention.